Análise da efetividade de gestão das Áreas de Proteção Ambiental Marinhas do estado de São Paulo/Brasil - Oliveira, Ana Paula Garcia de (2020)
The Brazilian Coastal and Marine Zone is approximately 10,800 km long, reflecting the great diversity of ecosystems and species present in the coastal / marine territory. The Protected Areas is internationally recognized as one of the main conservation instruments. Management effectiveness is defined as an assessment of the success of the management of protected areas, verifying if the management actions are fulfilling the objectives of creating the UC and managing to protect environmental and social factors. The objectives of this study are (1) to analyze the management effectiveness of the Marine APAs in the State of São Paulo, indicating the management actions that should be prioritized and suggesting recommendations for management measures that contribute to the effectiveness of the UCs (2) elaborate the definition of management effectiveness for Marine APAs, based on the main positive and negative points identified in this study. The methodology used was the RAPPAM Method (Rapid Assessment and Prioritization of Management of Conservation Units). The results show that the management effectiveness of the 3 Marine APAs is average, and the management planning, performance of the Managing Councils and communities and the internal organization of the UC are the indicators that enhance management. The best performance was obtained in the Planning element, while the Inputs element was the one that obtained the lowest results. Investing in inputs is essential so that the other elements of management effectiveness can be improved. The recommendations for management measures were listed, based on the results of the pressures and threats and the information obtained from the results of the other elements of effectiveness. This study showed that the UCs seek to achieve the objectives of conserving natural resources, however the management results are compromised due, mainly, to the low investment of inputs. It is hoped that this current panorama of the effectiveness of the management of Marine APAs and how suggested management measures can improve the management of protected areas, an end that they achieve their creation objectives.